2017
DOI: 10.1017/s175173111600121x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the accuracy and precision of methane prediction equations for beef cattle fed high-forage and high-grain diets

Abstract: The study determined the performance of equations to predict enteric methane (CH 4 ) from beef cattle fed forage-and grain-based diets. Many equations are available to predict CH 4 from beef cattle and the predictions vary substantially among equations. The aims were to (1) construct a database of CH 4 emissions for beef cattle from published literature, and (2) identify the most precise and accurate extant CH 4 prediction models for beef cattle fed diets varying in forage content. The database was comprised o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Examples of metaanalyses focussed on mitigation strategies include Ungerfeld et al (2007), Beauchemin et al (2008), Eugène et al (2008), Grainger and Beauchemin (2011), Jayanegara et al (2011), Patra (2013, Hristov et al (2013a) and the more recent papers by Veneman et al (2016) and Escobar-Bahamondes et al (2017). Ramin and Huhtanen (2013) estimated beef cattle MY as 21.9 g/kg DMI from their meta-analysis of five beef papers (Kirkpatrick et al 1997;Kurihara et al 1999;McGinn 2005, 2006;Beauchemin et al 2007).…”
Section: Other Methane Meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of metaanalyses focussed on mitigation strategies include Ungerfeld et al (2007), Beauchemin et al (2008), Eugène et al (2008), Grainger and Beauchemin (2011), Jayanegara et al (2011), Patra (2013, Hristov et al (2013a) and the more recent papers by Veneman et al (2016) and Escobar-Bahamondes et al (2017). Ramin and Huhtanen (2013) estimated beef cattle MY as 21.9 g/kg DMI from their meta-analysis of five beef papers (Kirkpatrick et al 1997;Kurihara et al 1999;McGinn 2005, 2006;Beauchemin et al 2007).…”
Section: Other Methane Meta-analysesmentioning
confidence: 99%
“…Escobar- Bahamondes et al (2017) recently evaluated MP prediction equations from five studies (Ellis et al 2007(Ellis et al , 2009Yan et al 2009;Ricci et al 2013;Moraes et al 2014). Only Ricci et al (2013) and Yan et al (2009) are included in MitiGate and they are not beef cattle studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escobar-Bahamondes et al (2017a) showed that many equations lacked accuracy, as they were not specific for high-forage or high-grain diets. According to that study, a set of equations was identified that predicted CH 4 production as well as or better than the IPCC Tier 2 methodology.…”
Section: )mentioning
confidence: 99%
“…Empirical models specifically for beef cattle (e.g., Ellis et al 2007Ellis et al , 2009Yan et al 2009;Muir et al 2011;Moraes et al 2014), for beef and dairy cattle (e.g., Ricci et al 2013;Ellis et al 2014), or for beef and dairy cattle and sheep (Ramin and Huhtanen 2013) have been proposed. However, the uncertainty of estimates of eCH 4 from beef cattle using these models can be substantial (Hippenstiel et al 2013;Moraes et al 2014), especially for cattle fed high-grain diets (Escobar-Bahamondes et al 2016). Part of this uncertainty could be due to the limitations of the model, but variability can also be due to the limited number of records, regional representation of data, and statistical distribution or range of each variable within the development database.…”
Section: Introductionmentioning
confidence: 99%